ANALISIS SWOT UNTUK PENGEMBANGAN POTENSI DAN PELUANG PASAR KABUPATEN BLITAR YANG BERTUMPU PADA POTENSI SUMBERDAYA ALAM - Siti Rokhmi Fuadati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2008)
The development in Blitar regency is held by mapping based on each district’s  potency. However, the potency of its natural resources has not been optimally explored for industrial opportunity since  there are no supported  maintenance.  Result of the research shows that most of the potencies are in its natural resources. The market  opportunity  usually  encounters  the individual interest,  such as a broker who create the biggest profit margin. In contrast, the craftman society collects very minimum profit. In Fact,the human resource has its huge potency but it becomes a matter when there is no regeneration to  the youth.  In addition, institution corporation factors are neede  to increase the bargaining position of district potency. These factor are  highly expected to guarantee the prover price of the material.